A new cryptic species in the “Calcinus anani Poupin & McLaughlin, 1998” species complex (Decapoda: Anomura: Diogenidae): evidence from colouration and molecular genetics - Malay, Maria Celia (Machel) D.; Komai, Tomoyuki; Chan, Tin-Yam (Zootaxa, 2012)
A new species of Calcinus is described from western Pacific material, including specimens previously identified as Cal-cinus anani Poupin & McLaughlin, 1998. The new species C. fuscus n. sp. differs from C. anani in the colouration in life,and their specific distinction is genetically supported by the barcoding gene cytochrome oxidase I (COI). The two speciesalso have different geographic distributions, with C. fuscus n. sp. ranging from Japan to the Philippines, Papua New Guin-ea, and New Caledonia, while C. anani is restricted to French Polynesia. Moreover C. fuscus n. sp. is found at shallower depths than its sister species C. anani.